Halotolerant bacteria producing hydrolytic enzymes isolated from hot springs from Tarapoto - Peru - Borja, Jackelyn E (2012)
The aim of this study was to characterize halotolerant bacteria producing hydrolases of biotechnological interest isolated from hot springs from Tarapoto. For that, water samples were collected and plated on trypticase soy agar containing 5% sodium chloride at 37 °C for 24 h. 14 aerobic bacterial isolates were selected to show colonies of different size, colour and consistency, then morphological and physiological properties and hydrolytic capacity to tween 80, starch, gelatin, carboximetilcellulose, lactose were determined. The 14 isolates were grouped according to substrate hydrolyzation profiles in groups: I (starch), II (lactose), III (Tween 80 and gelatin) , IV (tween 80 and starch ), V (starch, gelatin, lactose), VI (tween 80, starch and gelatin) corresponding in number of bacteria 1; 1; 1; 5; 1,5; respectively. 86% (12/14) of isolates hydrolyzed more than one substrate, but none carboxymethylcellulose, 93% (13/14) were bacilli, grew optimally between 30 and 40 °C at pH between 5 and 8, all formed colonies of rubbery consistency. The cultural characteristics of the isolates and the hydrolyzed substrate profiles indicate that there are at least 6 species or bacterial strains producing hydrolytic ezymes of great industrial potential.